Resuming clinical teaching in the era of COVID-19 : experiences and protocols from a dental school in Malaysia - Mohd Zamri Hussin; Mohideen Salihu Farook; Nor Azlida Mohd Nor; Firdaus Hariri; Kathreena Kadir; Nor Nadia Zakaria; Muhammad Kamil Hassan; Wan Nurazreena Wan Hassan (Penerbit Universiti Kebangsaan Malaysia, 2021)
The rapid spread of the global pandemic COVID-19 had challenged the Malaysian Healthcare and Education Systems. Teaching and learning at dental schools across the country were drastically changed to online approach as the nation enforced Movement Control Order (MCO). However, translation of psychomotor skills still require hands-on approach to produce competent dentists upon graduation, but most dental schools were not prepared for the prevention of COVID-19 transmission that require more strict cross infection protocol. The aim of this paper was to describe the response by a dental school in Malaysia to COVID-19 in modifying the clinical teaching and learning, infrastructure, facilities, and clinical services, and enhancing the infection control protocol through risk assessment of COVID-19 transmission and prevention strategies. The paper also discusses the limitations of our approach, challenges in providing clinical services and supervision as well as implications of changes to our practice. In conclusion, COVID-19 has modified the delivery and implementation of clinical teaching and learning in Malaysia. However, within the limited fund and resources, dental teaching institutions need to adapt to the new normal clinical environment in order to ensure that dentals students graduate on time with sufficient clinical training.